The Monomer Elution of Bulk-Fill Sculptable Composite and Flowable Composite after Photopolymerization - Nanik Zubaidah; Adioro Soetojo; Kun Ismiyatin; Karina Erda Saninggar; Hendri Eko Wahyudi; Sylvia; Sandra Kartika Sari (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Composite resins have excellent mechanical properties, including fast polymerization,aesthetic quality, easy handling, and the ability to adhere to the enamel surfaces. However, there are alsosome disadvantages from this material, one of them is residual monomers. Bulk-fill composite resins areavailable in sculptable (solid) and flowable (liquid) form. Most composite resin matrix is aromatic oraliphatic acrylates. Bis-GMA, UDMA, and TEGDMA are the matrix monomers that are commonly used butshow a high cytotoxicity level. They also have poor mechanical properties such as wear resistance, hardness,tendency to change color, and may cause pulp reactions. Aim: The aim of this study was to investigate thenumber of residual monomers in bulk-fill sculptable and flowable composites in the submersion of 75%ethanol solution (10 minutes, an hour, and 24 hours). Methods: Sculptable and flowable composites wereused in this study. Samples (4 mm thick, 5 mm diameter) were prepared and polymerized for 10 secondswith an intensity of 1025 mW / cm2 of a light emitted diode (LED). After the sample was made, each samplewas immediately immersed in a 75% ethanol solution as an extraction liquid and stored in amber-coloredbottles at room temperature. Samples were taken as many as 7 cc at intervals of 10 minutes, an hour, and 24hours. Samples were analyzed by High-Performance Liquid Chromatography (HPLC). The data obtainedwere analyzed using the Kruskal-Wallis Test, Independent T-Test and Mann-Whitney Test at a significancelevel of p <0.05. Result: The amount of elusion remaining monomers of the bulk-fill flowable compositewas higher than bulk-fill sculptable composite. UDMA composite of bulk fill flowable submersed in 75%ethanol solution for 24 hours was the highest among other monomers. Conclusion: Residual monomerseluted inside bulk-fill composite resins in all time periods and the amount of eluted monomers increaseswith time.